Upaya Penguatan Kapasitas Kelembagaan Pamong di Kalurahan Condongcatur - Abdillah, Ashar; Muhammad, Adji Suradji (Program Pasca Sarjana Universitas Garut, 2024)
The quality of public services cannot be separated from the quality of the apparatus providing the services. The limitations of human resources providing public services at the village level are determined by various factors. This research aims to find out the strategy of the Condongcatur Village Government in improving the quality of human resources who serve as officers to provide optimal public services. By using a qualitative research model, the Phenomonology model is supported by qualified informants starting from the Village Head, Carik, Jogoboyo, Management, Village Staff and also Village Assistants. Apart from qualified informants, researchers also use observation results and documentation to support the analysis. The research results show that the strategy carried out by the Condong Catur District Government is carried out through 4 main stages. Firstly through transparent and accountable recruitment, secondly through Technical Guidance to strengthen tasks and functions, thirdly through further studies and fourthly through intensive coordination patterns.